Performance Comparison Between Laravel and ExpressJs Framework Using Apache JMeter - Mangapul Siahaan; Wijaya, Ricky Wijaya (Universitas Medan Area, 2024)
Modern web application development requires selecting an optimal framework to ensure maximum efficiency and performance. This research compares two leading frameworks, Laravel (using PHP) and Express.js (using JavaScript), in the context of building RESTful APIs. The purpose of this research is to compare the performance of Laravel and Express.js through performance testing, with a focus on the API response to student data access in the MySQL database. The research method used is performance testing which involves realistic test scenarios and performance metrics such as response time. The research results provide a deep understanding of the performance advantages and disadvantages of Laravel and Express.js in API development. This research helps developers choose a framework that suits project needs, considering efficiency and speed in developing RESTful APIs. The test results show the superiority of the Laravel framework with an average response time of 1745.7 ms faster than Express.js. This Laravel is better suited for applications with high concurrent user access, while Express.js is a good choice for applications with a lower number of simulated users. Framework selection must consider both response speed and specific application needs and consider the specifications of the server used. The implication of this research can help developers optimize web application development, increase efficiency, and ensure maximum performance according to the project goals